Prognostic Utility of Morning Blood Pressure Surge for 20‐Year All‐Cause and Cardiovascular Mortalities: Results of a Community‐Based Study - Hao‐Min Cheng; Chung‐Li Wu; Shih‐Hsien Sung; Jia‐Chun Lee; Kazuomi Kario; Chern‐En Chiang; Chi‐Jung Huang; Pai‐Feng Hsu; Shao‐Yuan Chuang; Edward G. Lakatta; Frank C. P. Yin; Pesus Chou; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundMorning blood pressure (BP) surge (MS), defined by the MS amplitude, is an independent prognostic factor of cardiovascular outcomes in some, but not all, populations. Method and ResultsWe enrolled 2020 participants (1029 men; aged 30–79 years) with 24‐hour ambulatory BP data. During a median 19.7‐year follow‐up, 607 deaths (182 by cardiovascular causes) were confirmed from the National Death Registry. The amplitude of sleep‐trough MS (STMS) was derived from the difference between morning systolic BP (SBP) and lowest nighttime SBP. The rate of STMS was derived as the slope of linear regression of sequential SBP measures on time intervals within the STMS period. Thresholds for high STMS amplitude and rate were determined by the 95th percentiles (43.7 mm Hg and 11.3 mm Hg/h, respectively). Multivariable Cox models, adjusting for age, sex, body mass index, smoking, alcohol, low‐density lipoprotein cholesterol, 24‐hour SBP, night:day SBP ratio, and antihypertensive treatment, revealed that a high STMS rate (hazard ratio, 1.666; 95% confidence interval, 1.185–2.341), but not STMS amplitude (hazard ratio, 1.245; 95% confidence interval, 0.984–1.843), was significantly associated with a greater mortality risk. Similarly, STMS rate (hazard ratio, 2.608; 95% confidence interval, 1.554–4.375), but not STMS amplitude, was significantly associated with the risk of cardiovascular mortality (hazard ratio, 0.966; 95% confidence interval, 0.535–1.747). Moreover, the prognostic values of STMS rate were comparable in subjects with or without morning and nocturnal hypertension (P>0.05 for interaction for all). In simulation studies, STMS rate was less susceptible to measurement errors of the sleep‐trough SBP than STMS amplitude. ConclusionsSTMS rate could independently help identify subjects with an increased cardiovascular risk.